EFEKTIVITAS PENGGUNAAN LIMBAH SERBUK GERGAJI POHON NANGKA (Artocarpus heterophyllus L.)SEBAGAI ALTERNATIF PEMBUATAN INDIKATOR ASAMBASA - Martina Retnoyuanni, Friyatmoko Wahyu K., Arif Hidayat, (Pelita - Jurnal Penelitian Mahasiswa UNY, 2008)
This research aims at knowing the making of natural acid-base indicatorfrom jackfruit sawdust, the use of acid-base indicator from the jackfruit sawdust,the color change shown by acid-base indicator from jackfruit sawdust, and knowingthe pH trayek on the acid-base indicator from jackfruit sawdust.This research was conducted in Chemistry-physic laboratory on July 2008.The research method involved the making of acid-base indicator from jackfruitsawdust and the making of pH trayek.The result of the research shows that (1) acetone solvent can produce abetter indicator than alcohol one; (2) acid-base indicator can differentiate solutionfrom pH 7 to pH 10, pH 11, dan pH 12; (3) the higher pH the darker the browncolor; (4) pH trayek which is produced from the indicator of jackfruit sawdust isfrom light brown to dark brown.Key words: pH indicator, jackfruit, morin